41/77
\begin{frame}
  \frametitle{Examples}

  \begin{exampleblock}{$R(a,b) \;\vdash\; \myex{x}{\myex{y}{R(x,y)}}$}
  \begin{tikzpicture}
    \naturaldeduction{
      \proofstep{$R(a,b)$}{premise};   
        \proofstep{$\myex{y}{R(a,y)}$}{$\exists i\;$ 1};
         \proofstep{$\myex{x}{\myex{y}{R(x,y)}}$}{$\exists i\;$ 2};
    }
  \end{tikzpicture}
  \end{exampleblock}
  \pause\medskip
  
  \begin{exampleblock}{$R(a,\alert{a}) \;\vdash\; \myex{x}{\myex{y}{R(x,y)}}$}
  \begin{tikzpicture}
    \naturaldeduction{
      \proofstep{$R(a,a)$}{premise};   
        \proofstep{$\myex{y}{R(a,y)}$}{$\exists i\;$ 1};
         \proofstep{$\myex{x}{\myex{y}{R(x,y)}}$}{$\exists i\;$ 2};
    }
  \end{tikzpicture}
  \end{exampleblock}
\end{frame}